Descartes' system of natural philosophy - Gaukroger, Stephen (Cambridge University Press, 2002)
Towards the end of his life, Descartes published the first four parts of a projected six-part work, The Principles of Philosophy. This was intended to be the definitive statement of his complete system of philosophy, dealing with everything from cosmology to the nature of human happiness. Stephen Gaukroger examines the system, and reconstructs the last two parts, "On Living Things" and "On Man", from Descartes' other writings. He relates the work to the tradition of late Scholastic textbooks which it follows, and also to Descartes' other philosophical writings.